Investigation of the dimensionality of charge transport in organic field effect transistors - Abdalla, Hassan; Fabiano, Simone; Kemerink, Martijn (Physical review, 2017)
Ever since the first experimental investigations of organic field effect transistors (OFETs) the dimensionality of charge transport has alternately been described as two dimensional (2D) and three dimensional (3D). More recently, researchers have turned to an analytical analysis of the temperature-dependent transfer characteristics to classify the dimensionality as either 2D or 3D as well as to determine the disorder of the system, thereby greatly simplifying dimensionality investigations. We applied said analytical analysis to the experimental results of our OFETs comprising molecularly well-defined polymeric layers as the active material as well as to results obtained from kinetic Monte Carlo simulations and found that it was not able to correctly distinguish between 2D and 3D transports or give meaningful values for the disorder and should only be used for quasiquantitative and comparative analysis. We conclude to show that the dimensionality of charge transport in OFETs is a function of the interplay between transistor physics and morphology of the organic material.